Preeclampsia prevention (Colombia Medica, 2016)
Colombia and Brazil are developing countries where pregnancy-related hypertensive disorders and associated conditions constitute major concerns in public health area. Calcium plus conjugated linoleic acid used by pregnant adolescents had preventive effect on PE, but the prevention did not occur with utilization of calcium alone. After implementation of Colombian prenatal care program based on the bio-psychosocial model, maternal mortality and the rate of PE reduced in 23% and 22%, respectively. Late postpartum eclampsia, is the onset of seizuress more than 48 hours, but less than four weeks after delivery. This severe condition may occur without antecedent of PE. Lower maternal mortality due to preeclampsia/ eclampsia can follow implementation of prenatal programs based on BPSM, and use of calcium plus conjugated linoleic acid